The Impact of Industrial Policy on Export Diversification: Some Empirical Evidences from Pakistan - Azam, Amir (Technium Social Sciences Journal, 2021)
Export sector is considered as the backbone of any economy. The economy which is efficient and competitive in global market enjoys better export performance otherwise become dependence on foreign goods market. Pakistan being a developing economy faces worse export performance as compare to its past competitors and currently economy faces huge current account deficit. The current study made an attempt to check the relationship between Industrial Policy and export diversification using ARDL approach because of different integration nature of variables under consideration from 1980-2018. The findings of the study suggests that there is strong relationship between industrial Policy instruments and export diversification both in short run and long run and by enhancing strong and visionary Industrial Policies and less relying on imports, the economy can enjoy sufficient growth and diversify its export structure.